Competion, Diffidence, and the Loss of Enjoyment. An Aspect of Hobbes' Leviathan - Mauro Basaure (Ideas y Valores, 2015)
According to Hobbes, competition and diffidence are basic sources of aggression. The paper argues that different logics are involved in these causes of quarrel. While competition leads to concrete aggression, motivated by a desire for objects based on the senses, diffidence requires a greater cognitive effort and leads to aggression against others considered as potential enemies. In the latter case, objects matter as a means to future safety, through the anticipation of and the struggle for power, deemed to be prototypes of rational action. In this respect, the enjoyment of objects tends to be relegated to the sphere of irrationality. The novelty of our approach lies in making evident the issue and some of its consequences.